COMPREHENSIVE REVIEW OF AIRWAY MANAGEMENT TECHNIQUES IN EMERGENCY MEDICAL SERVICES. - Faisal Abdullah Hamdi, Hatim Abdullah Al-Baqami, Ziyad Abdulrahman Alajaji, Turki Mohmmad Alotaibi, Satam Mutlaq Alotaibi, Rayan Ahmed Hasaan Ibrahim, Yasser Nashi Alrooqi, Mazen Hasaan Asiri, (Chelonian Research Foundation, 2022)
It is critical for the EMS system to practice efficient airway management to obtain the best results in patient emergencies. This all-encompassing review examines methods of airway management in EMS, including intubation through the larynx, supraglottic airway gadgets, and bag, valve, and mask ventilation. The key points, such as the indications for, the contraindications for, the complications to watch out for, and the evidence-based practices, are also treated. Besides that, the codswallop includes enhancing airway management technology through simulation training, which increases providers' competence. The article provides clinical recommendations on how EMS services could enhance airway management, focusing on the ultimate goal of patient care. Keywords: Airway management, emergency medical services, endotracheal intubation, supraglottic airway devices, bag-valve-mask ventilation, simulation training.